The influence of displacement damage on helium uptake and retention in tungsten. (March 2023) - Kärcher, A.; Schwarz-Selinger, T.; Burwitz, V.V.; Mathes, L.; Hugenschmidt, C.; Jacob, W.
Highlights: Displacement-damaged and undamaged samples exposed to 10 18 He/m 2 s with 100 eV. He retention lower by factors 3–100 compared with literature data using 300–500 eV He. He depth profiling by elastic recoil detection and erosion via anodic oxidation. Deeper He penetration for undamaged samples compared with pre-damaged samples. He self-trapping or trap-mutation do not dominate for these He fluxes. Abstract: The influence of pre-existing displacement damage on the early stages of helium (He) interaction with tungsten (W) and the resulting defect creation was investigated experimentally. Samples were irradiated with 20.3 MeV W ions to different damage levels of 0.004, 0.01 and 0.1 displacements per atom (dpa). Displacement-damaged and undamaged W samples were exposed to a He plasma at room temperature at He fluxes of 1.2–1.8 × 10 18 He/m 2 s to fluences of up to 10 22 He/m 2 . He ion energy of 100 eV was used to remain well below the threshold for displacement damage creation in the bulk. Elastic recoil detection analysis (ERDA) shows that the He retention in the damaged samples is up to one order of magnitude larger than in the undamaged sample. Compared with the W samples exposed to He with energies of 300 – 500 eV in literature, the data in this study shows substantially lower He retention. Detailed He depth distributions were derived by stepwise removal of thin surface layers (via anodic oxidation and dissolution of the oxide) and subsequent ERDA measurements of the remaining He content. Pre-damaged samples show a significantly faster decrease in He concentration with depth than the undamaged sample, indicating that He is efficiently stopped by pre-existing defects from diffusing into deeper regions beyond 34 nm. The undamaged sample exhibits a lower He concentration in the near surface region and a flatter distribution of He up to a depth of 100 nm. The characterization of samples before and after He plasma exposure by Doppler broadening spectroscopy of the positron annihilation line (DBS) gives no indication for self-trapping or trap-mutation in both the pre-damaged and the undamaged samples. From the clear influence of the initial displacement damage level on the He uptake and retention we conclude that He self-trapping mechanisms have a negligible, if any, effect on the He diffusion depth in W at fluxes of 1.2–1.8 × 10 18 He/m 2 s.